Early-phase Innate Immune Suppression in Murine Severe Sepsis Is Restored with Systemic Interferon-β. (July 2018) - Kusakabe, Yoshiomi; Uchida, Kanji; Yamamura, Yoshiro; Hiruma, Takahiro; Totsu, Tokie; Tamai, Yuho; Tsuyuzaki, Hitoshi; Hasegawa, Kyoko; Chang, Kyungho; Yamada, Yoshitsugu
Abstract : Background: Sepsis is a leading cause of death in the intensive care unit. Immune modulatory therapy targeting sepsis-associated proinflammatory responses has not shown survival benefit. Here, the authors evaluated innate immunity at the early stage of murine mild or severe peritoneal sepsis induced by cecal ligation and puncture, and the effect of systemic interferon-β, a potent inflammatory mediator, on severe sepsis as well as its mechanism of action. Methods: Mild and severe sepsis was induced in C57BL/6 mice by cecal ligation and puncture with 22- and 18-gauge needles for puncture, respectively. Interferon-β (700 U/g) was subcutaneously administered either before or 12 h after cecal ligation and puncture for the severe sepsis group. Results: Severe sepsis resulted in significantly lower 6-day survival rates than mild sepsis (n = 48, 25% vs . n = 11, 81.8%, P = 0.002), significantly less phagocytic capacity of peritoneal exudate cells, and lower CXC chemokine receptor-2 expression on circulating neutrophils at 24 h after cecal ligation and puncture. Interferon-β administration 12 h after cecal ligation and puncture associated with significantly improved survival (n = 34, 52.9%, P = 0.017) increased the number and function of peritoneal exudate cells, peritoneal/systemic inflammatory cytokine/chemokine concentrations, and CXC chemokine receptor-2 on neutrophils, compared with the severe sepsis controls. However, those responses were not observed in the prophylactic interferon-β group (n = 24). Interferon-β increased lipopolysaccharide-induced interleukin-6 messenger RNA/protein expression of lipopolysaccharide-tolerant murine peritoneal macrophages, which was not observed in nontolerant cells. Conclusions: In severe sepsis, immune suppression occurs within 24 h and is associated with worse mortality. Interferon-β given after the onset of peritonitis restores impaired innate immunity in vivo and in vitro . Abstract : In an established mouse model of sepsis (cecal ligation and perforation), severe versus mild sepsis was associated with increased mortality, less capacity of peritoneal inflammatory cells for phagocytosis, and decreased expression of focal and systemic cytokines and chemokine receptor expression on circulating neutrophils. These effects were reversed by the administration of the immune stimulant interferon-β after—but not before—severe sepsis was established. Interferon-β after the onset of peritonitis may restore impaired innate immunity and improve outcome.Supplemental Digital Content is available in the text.